BEKAL BERGIZI SEIMBANG BAGI ANAK SEKOLAH DASAR KELAS 6 SD NEGERI GALUNGGUNG TASIKMALAYA - Lestari, Nia; Fathiyah, Aisyah Putri; Nafisah, Dewi; Amini, Fadhilah; Salsabila, Karina; Azzahra, Siti Fadillah (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2023)
Abstract: School-age children are one of the age groups that are very vulnerable to nutritional and health problems because at school age the development of bones, teeth, muscles, and blood occurs so they need more nutritional intake compared to the adult group. Elementary school-aged children spend a third of their time at school. Bringing lunch from home can make it easier for children to monitor the nutritional content, hygiene, and cleanliness of the food consumed by children, and can prevent unhealthy snacking habits at school. This counseling activity raises the issue of school-age children who need balanced nutritional intake but often their needs are not met due to their picky eating habits. This service aims to introduce students to a dish that already contains a variety of nutritional needs and is easy for children to make at their age. The dishes are arranged in a bento which is created so that it can further arouse the students' appetite. Pre-implementation activities begin with product trials and preparation of booklets and materials that will be given to students. The implementation stage, namely the students listened to the presentation of material on balanced nutrition, examples of nutrients, the negative impact if nutritional needs were not met, Bento lunch boxes, and closed with a quiz with prizes to find out how far the students' understanding of the material explained by the implementation team continued with a demonstration of cooking one example of a balanced nutritious lunch, and ended with an evaluation of the results of the demonstration and the results of the competition by the homeroom teacher. The expected outputs are service articles published in national service journals, news on the implementation of community service in online mass media, HKI, and community service booklet products. Abstrak: Anak usia sekolah adalah salah satu kelompok umur yang sangat rentan mengalami permasalahan gizi dan kesehatan, karena pada usia sekolah terjadi perkembangan tulang, gigi, otot, darah sehingga mereka membutuhkan lebih banyak asupan gizi dibandingkan dengan kelompok dewasa. Anak usia sekolah dasar menghabiskan sepertiga waktunya di sekolah. Membawa bekal dari rumah dapat membuat makanan yang dikonsumsi oleh anak menjadi lebih mudah dipantau kandungan gizinya, higiene dan kebersihannya, serta dapat menghindari kebiasaan jajan yang kurang sehat di sekolah. Kegiatan penyuluhan ini mengangkat permasalahan anak usia sekolah yang membutuhkan asupan nutrisi yang bergizi seimbang namun sering kali kebutuhannya tidak terpenuhi dikarenakan kebiasaan mereka yang memilih milih makanan. Pengabdian ini bertujuan ingin mengenalkan kepada para siswa salah satu hidangan yang sudah mengandung berbagai macam kebutuhan nutrisi dan mudah dibuat oleh anak di usianya. Hidangan tersebut disusun dalam sebuah bento yang dikreasikan sehingga dapat lebih menggugah selera makan para siswa. Kegiatan pra pelaksanaan diawali dengan ujicoba produk dan penyusunan booklet serta materi yang akan diberikan kepada para siswa. Tahap pelaksanaan yaitu para siswa menyimak penyampaian materi mengenai gizi seimbang, contoh-contoh zat gizi, dampak negatif apabila kebutuhan gizi tidak terpenuhi, bekal makan Bento, dan ditutup dengan quiz berhadiah untuk mengetahui seberapa jauh pemahaman para siswa mengenai materi yang sudah dijelaskan oleh tim pelaksana dilanjutkan demonstrasi memasak salah satu contoh bekal bergizi seimbang, dan diakhiri dengan kegiatan evaluasi hasil demonstrasi dan hasil lomba oleh wali kelas. Luaran yang diharapkan adalah artikel pengabdian yang dipublikasikan pada jurnal pengabdian nasional, berita pelaksanaan pengabdian di media massa online, HKI, dan produk booklet media pengabdian.